Geomagnetic control of the midlatitude daytime foF1 and foF2 long‐term variations: Physical interpretation using European observations. Issue 7 (28th July 2016) - Mikhailov, A. V.; Perrone, L.
Abstract: Morphological analysis of Slough/Chilton and Juliusruh fo F 2 and fo F 1 long‐term variations for the period including recent observations made in the previous paper (PM) has shown that the geomagnetic control is valid in the 21st century, moreover, the dependence on geomagnetic activity has become more pronounced and explicit after 1990. A new method to retrieve thermospheric neutral composition (O, O2, and N2 ), exospheric temperature T ex, and the total solar EUV flux with λ < 1050 Å from routine fo F 1 ionosonde observations has been developed to understand the mechanism of this geomagnetic control. The method was tested using CHAMP/STAR neutral gas density measurements. The retrieved for the first time thermospheric parameters at Slough/Chilton and Juliusruh over the period of 5 solar cycles were used to analyze the mechanism of fo F 1 and fo F 2 long‐term variations in the light of the geomagnetic control concept. It was shown that the control was provided via two channels: [O] and [O]/[N2 ] variations. Geomagnetic activity presented by 11 year running mean weighted index Ap 11y controls the (O/N2 )11y ratio variations, while solar activity presented by ( F 10.7 )11y controls atomic oxygen [O]11y variations. Atomic oxygen, the main aeronomic parameter controlling daytime fo F 1 and fo F 2 variations, manifests solar cycle and long‐term (for some solar cycles) variations with the rising phase in 1965–1985 and the falling phase in 1985–2008. These long‐term [O] variations are reflected in fo F 2 and fo F 1 long‐term variations. The origin of these long‐term variations is in the Sun. The empirical thermospheric model Mass Spectrometer Incoherent Scatter‐86 driven by Ap and F 10.7 indices manifests [O]11y and (O/N2 )11y variations similar to the retrieved ones including the period of deep solar minimum with a very low atomic oxygen concentration in 2008. This confirms the basic idea of the geomagnetic control concept that ionospheric long‐term variations have a natural (not anthropogenic) origin related to long‐term variations in solar and geomagnetic activity. Key Points: A new method to retrieve thermospheric parameters from routine fo F 1 ionosonde observations Atomic oxygen demonstrates solar cycle The negative fo F 2 trend commonly discussed in literature was due to a very long‐term decrease in the atomic oxygen abundance